Pelatihan Manajemen Bisnis Kedelai dalam Meningkatkan Kualitas Produk bagi Pelaku Usaha Kedelai di Purwakarta - Destiana Utarinda; Rofiq Noorman Haryadi; Muhammad Salman Al Farisi; Ali Mutaufiq; Eliza Eliza (Universitas Muhammadiyah Semarang, 2022)
The purpose of this community service activity is to provide soybean nursery business management training to help reduce the rate of soybean imports in Indonesia and provide soybean nursery training using F.T.A Serum to empower the people of Purwakarta. The method used in this community service activity is training and program socialization carried out by the community service team as well as assistance in evaluating activities. In addition, the service team also provides assistance to the management of soybean cultivation to the community, especially soybean business actors by using different planting media. The next method is to provide information related to soybean seeding by experts from PT. Dwitunggal Nusa Mandiri and conducts nursery business management training for business actors as well as human resource management. The result of this community service activity is that the management of the soybean nursery business using F.T.A serum has succeeded in increasing the number of harvests in each period. The community gave a very positive response to this community service activity because this activity was very beneficial for soybean business actors in Purwakarta..